The Effect Of Internal Auditor Independene On Effectiveness Of Government Internal Audit: Group Cohesiveness As An Intervening Variable (Case Study At The Regional Inspectorates At Java Island) - Moh. Ubaidillah; Ari Kuncara Widagdo (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
The objective of this study is to examine the effect of auditor independence, group cohesiveness, and individual factors on internal audit effectiveness of regional inspectorates. In addition, this study also intends to examine whether group cohesiveness mediates relationship between auditor independence and internal audit effectiveness. Population of this study is regional inspectorates located in some regencies/municipalities in Central Java Province and East Java Province, Indonesia. Method of analysis of this study is structural equation modeling by using Smart PLS. The results indicate that, as predicted, auditor independence has a positive and significant relationship with internal audit effectiveness. Interestingly, this study proves that group cohesiveness partially mediates relationship between auditor independence and internal audit effectiveness. Unfortunately, individual factors (i.e. level of education and work experience) do not have significant relation with audit effectiveness.